The Impact of Abdominal Core Stability Exercise Therapy on Enhancing Sitting Balance and Hand Function in Cerebral Palsy Patients - Abdullah, Khabib; Swandari, Atik; Sahla, Shabrina; Wijaya, Aji Sukma (GLOBAL HEALTH SCIENCE GROUP, 2025)
Cerebral palsy (CP) is a disorder of posture and movement control in children during growth and development. One of the problems in children with CP is impaired sitting balance which results in weakness of hand function such as holding and manipulating objects. Objective: to determine the effect of abdominal core stability exercise therapy on improving sitting balance and functional hand abilities of children with CP at YPCP Surabaya. Method: an experimental study with one treatment group, the study's population consisted of 20 children with cerebral palsy (CP) who were in the sitting training phase at YPCP Surabaya. Using purposive sampling with specific inclusion and exclusion criteria, 18 participants were selected from the group. The treatment was abdominal core stability exercise therapy consisting of myofascial release of back muscles, trunk mobilization, sitting upright on a bench with feet on the floor, and moving toys with both hands in an upright sitting position. Exercise therapy was carried out for 30 minutes 3x per week for 12 weeks. The measuring instrument for sitting balance was TCMS (trunk control measurement scale) and the hand function was Melbourne Assessment 2. Result: 18 children with CP in the sitting exercise phase (12 boys and 6 girls) with an average age of 4.1 ± 1 years. The mean static sitting balance increased from 2.7 to 14.1 (p=0.000), the mean dynamic sitting balance rose from 0.00 to 3.3 (p=0.000), the mean reactive balance increased from 0.0 to 0.5 (p=0.3) and the mean functional hand ability increased from 6 to 7.4 (p=0.001). Conclusion: Abdominal core stability exercise therapy improves static, dynamic sitting balance and functional hand ability in children with CP at YPCP Surabaya, but not reactive balance.